RAW 264.7 대식세포에서 lipopolysaccharide로 유도된 산화스트레스에 대한 참깨박과 들깨박 추출물의 저해 효과 비교 - 배현아(Hyeon-A Bae); 김춘영(Choon Young Kim) (한국식품과학회지, 2023)
Sesame seed meal (SSM) and perilla seed meal (PSM) are by-products of oil products inevitably massproduced and discarded every year. Valorization of these agricultural by-products is an effective strategy for sustainable food supply. This study explores the potential of by-products, SSM and PSM, emphasizing their antioxidant properties. Comparative analyses revealed higher protein content in PSM, while SSM exhibited superior browning index and Hunter’s color values. Antioxidant assays indicated higher radical scavenging activity and phenolic contents in PSM. Both SSM and PSM mitigated LPS-induced nitric oxide and reactive oxygen species production in RAW 264.7 cells in a dose-dependent manner. Consistent with these results, SSM and PSM treatments elevated LPS-lowered gene levels of key antioxidant enzymes including glutathione peroxidase-1, superoxide dismutase-1, and catalase. This study highlights the underutilized potential of SSM and PSM, underlining their value in functional food applications. KCI Citation Count: 0